Desain Sistem Monitoring Kelembapan Tanah, Suhu, dan Intensitas Ultraviolet Menggunakan Arduino Mega 2560 Berbasis Internet of Things (IoT) - Pramono, Subur; Ulum, Miftahul; Rudiana; Safitri, Ramona Dyah (Universitas Islam Negeri Alauddin Makassar, 2024)
We have successfully developed a monitoring system of soil moisture, temperature, and ultraviolet based on the Internet of Things (IoT) using Arduino Mega 2560. The sensors used to measure soil moisture, temperature, and ultraviolet are the soil moisture sensor, DHT-11 sensor, and GY-ML8511 sensor. Node MCU ESP8266 application is used to communicate between Arduino Mega 2560 and smartphones. Outputs of soil moisture sensors are connected to the water pump and blower. The water pump is on when soil moisture is below 60% and else it is off, the blower is on when soil moisture is above 80%. In this study, we don’t use the time parameter in the water pump or blower. Meanwhile, temperature and ultraviolet sensors were just used to monitor the system considered. The largest ultraviolet intensity measured by ML8511 sensors is squared at the value ADC is 123 and voltage 1,01V. Based on the testing system, it was obtained that the system is optimally operated